2016
DOI: 10.2105/ajph.2016.303429
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Two Adolescent Pregnancy Prevention Interventions on Risky Sexual Behavior: A Three-Arm Cluster Randomized Control Trial

Abstract: Objectives. To test the efficacy of Reducing the Risk (RTR) and Love Notes (LN) on reducing risky sexual behavior among youths yet to experience or cause a pregnancy. Methods. The four dependent variables were ever had sex, condom use, birth control use, and number of sexual partners at 3- and 6-month follow-up in a 3-arm cluster randomized controlled trial of 1448 impoverished youths, aged 14 to 19 years, in 23 community-based organizations in Louisville, Kentucky, from September 2011 through March 2014. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 13 publications
0
24
0
2
Order By: Relevance
“…First, the YREP did not include a control group nor employ an experimental design. Although other studies have used control groups and found positive effects with the Love Notes program (Barbee et al, 2016), it is difficult to eliminate factors beyond the Love Notes curriculum that influenced the present study's results, and there is uncertainty as to the directional nature of the relationship between hope and psychological distress due to completion of YREPs. Second, this study utilized two waves of data; thus, waning effects may have occurred with longer term follow-ups.…”
Section: Limitationsmentioning
confidence: 85%
See 1 more Smart Citation
“…First, the YREP did not include a control group nor employ an experimental design. Although other studies have used control groups and found positive effects with the Love Notes program (Barbee et al, 2016), it is difficult to eliminate factors beyond the Love Notes curriculum that influenced the present study's results, and there is uncertainty as to the directional nature of the relationship between hope and psychological distress due to completion of YREPs. Second, this study utilized two waves of data; thus, waning effects may have occurred with longer term follow-ups.…”
Section: Limitationsmentioning
confidence: 85%
“…Navigating romantic relationships influences factors associated with adolescent mental health (Collins et al, 2009). Romantic relationships have the potential to benefit (e.g., reduce feelings of isolation) and negatively impact (e.g., exposure to dating violence; Barbee et al, 2016) adolescents. Youth relationship education programs (YREPs) have been found to be a promising avenue to promote adaptive relationship knowledge, attitudes, and skills (Simpson et al, 2018); however, there may be a benefit to examining the processes by which YREPs influence global mental health outcomes (Wadsworth & Markman, 2012).…”
mentioning
confidence: 99%
“…There is preliminary evidence supporting the efficacy of youth relationship education programming. Early results suggest adolescent relationship education can reduce teen pregnancy rates and increase relationship knowledge, attitudes, skills, and behaviors within intimate relationships (Barbee et al, 2016 ; McElwain et al, 2017 ; Simpson et al, 2018 ). Some programs have also begun to incorporate a dual focus on alleviating relational stressors via relationship education and financial stressors via job‐skills training/financial literacy and subsidized education or job opportunities (Yazedjian, 2017 ).…”
Section: Recommendations For Future Intervention Work With Lower‐income Familiesmentioning
confidence: 99%
“…Teen pregnancy prevention programs described as innovative incorporated life planning and goal setting (Barbee, Cunningham, van Zyl, Antle, & Langley, 2016), cultural relevance and sensitivity (Jenner et al, 2016;Abe, Barker, Chan & Eucogco, 2016), technology (Kaufman, Schwinn, Black, Keane & Big Crow, 2016;Markham, et al, 2012;Bull et al, 2016, Downs et al, 2004, and holistic youth development approaches targeting adolescent risk behaviors (Piotrowski & Hedeker, 2016). Lessons learned related to the future implementation of these programs include the cost and time of program implementation, training of facilitators and staff, using hybrid approaches to tailor activities for participants, and incorporating culturally relevant stories/examples and values (Barbee, Cunningham, van Zyl, Antle, & Langley, 2016;Abe, Barker, Chan & Eucogco, 2016;Bull et al, 2016;Piotrowski & Hedeker, 2016;Downs et al, 2004). However, counter to the concept of rapidly capturing and prototyping ideas to programs (Wilson & Rosenberg, 1988), teen pregnancy prevention models have been slow in their uptake by organizations and facilitators outside government funded grantees (Rolleri, Wilson, Paluzzi & Sedivy, 2008).…”
Section: Innovation and Teen Pregnancy Prevention Programsmentioning
confidence: 99%